The IN-FAKT Study Protocol: Investigating the Experiences and Management of Individuals With Failing Kidney Transplants - Pippa Bailey; Lucy Selman; Catherine Exley; Sian Griffin; Alan Hancock; Paul Maxted; Jane Noyes (International Journal of Qualitative Methods, 2023)
Background : In the UK 1500 kidney transplants fail each year. 2% of living-donor transplants and 5% of deceased-donor transplants fail within a year of transplantation. Many decisions need to be made when a kidney transplant fails, including whether the transplant should be removed, and which immunosuppression medication should be stopped. There is limited evidence on which to base these decisions. We do not understand how decisions are made in the absence of good evidence, and there is national variation in practice. Aims : The overall aim is to develop a theory of patient and clinician transplant failure behaviours and decisions that will inform the design of a Randomised Controlled Trial (RCT) to evaluate treatments to optimise the management of transplant failure and improve outcomes for patients and their families. Methods : In a UK setting, we will develop a Constructivist Grounded theory using in-depth interviews with people over 18 years who are or have experienced kidney transplant failure, their families/close friends, and renal healthcare professional. Iterative purposive sampling of patients from different hospitals will be undertaken to achieve diversity with respect to age, sex, ethnicity, socioeconomic position, transplant type, and cause of transplant failure. Subsequent sampling will be theoretical, to test and develop hypotheses and theories being constructed. The sample size will be determined by reaching theoretical theme saturation with an anticipated minimum of 25–30 patients, 25–30 family members/close friends and 10–15 renal healthcare professionals. The research team will take a reflexive approach to make any influences or potential biases transparent. This knowledge will be used to develop the programme theory and design an RCT to evaluate treatments delivered at the right time in a patient’s journey, to improve experiences and outcomes for people with failing kidney transplants.